PENGARUH RELATIONSHIP MARKETING TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN KORAN RAKYAT BENGKULU - Oktariani, Yolanda; Yeyen Permayanti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
This study aims to determine the effect of customer satisfaction and corporate reputation on customer loyalty (study on customers of PT. JNE Bengkulu City). The population used in this study is all customers who use the services of PT. JNE Bengkulu City with a total sample of 120 respondents. Data collected through online questionnaires were then processed using the SPSS test tool version 26. The results of this study indicate that partially and simultaneously the Customer Satisfaction and Corporate Reputation variables have a significant positive effect on Customer Loyalty.